STUDI DESKRIPTIF GAYA EKSPLANATORI ANAK PENDERITA LEUKEMIA - Anna Maria Amanda Putri; Sianiwati Sunarto Hidayat; Eveline Sarintohe (Departemen Psikologi Universitas Pendidikan Indonesia, 2018)
This descriptive research conducted with 25 children under purposive sampling to obtain an overview of expanatory style of children with leukemia in the Foundation X Bandung. Measurement instrument is a modification of the Children's Attributional Style Questionnaire (CASQ) by Seligman (1990) which consists of 48 items forced choice. Explanatory style research showed that 60% respondents have a pessimistic, and the rest have an optimistic. There is a link between children's understanding of their significant person’s explanatory style, criticism from parents or the trustees, their crisis experience, as well as the stage of suffering from leukemia with the children with leukemia’s explanatory style. This research suggested further research with more sample sizes about children’s explanatory style in order to make normative constraints, also further investigate the factors that affect explanatory style and dimensions. It is also suggested that management of the Foundation X to design interventions that can improve children's explanatory style.